Bonsoir, J'ai un exercice à faire mais je bloque quelqu'un pourrait m'aider ?

Factoriser les expressions suivantes :

A = 4x²-25-(3x-1)(2x+5)

B = x²-4(2x+3)²

C = 9x²(x+2)-12x(x+2)+4x+8

D = x²+2x+1-16(4x²-20x+25)

E = (2x+1)(x-4)+2x(x+4)-5(x-1)

1

Réponses

2013-05-15T21:39:45+02:00

A = 4x²-25-(3x-1)(2x+5)

A = (2x+5)(2x-5) -(3x-1)(2x+5)

A = (2x+5)( 2x-5-3x+1)

A= (2x-5)( -x -4 ) 

 

B = x²-4(2x+3)²

B= (x+2)(x-2)(2x+3)²

 

 

C = 9x²(x+2)-12x(x+2)+4x+8

C= 9x²(x+2) -12(x+2) + 4( x+2)

C= (x+2) (9x² -12 +4)

C= (x-2) (9x²-8 )

 

D = x²+2x+1-16(4x²-20x+25)

D = (x+1)²- 16( 2x-5)²

 

E = (2x+1)(x-4)+2x(x+4)-5(x-1)

E = 2x² -8x +x -4 +2x² +8 -5x +5

E =4x² -4x +1

E = (2x - 1)²